Coherent quantum phenomena in mesoscopic metallic conductors (Review Article) - Gogadze, G.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2010)
The quantum coherent phenomena in mesoscopic cylindrical metallic conductors have been considered. Pure double-and single-connected normal samples were placed in a longitudinal magnetic field, which generated interference phenomena depending on the magnetic flux through the cross-section of the conductor. The period of the induced oscillations is equal to the flux quantum hc/e of the normal metal. The quantum states are formed in the structures by collisions of the electrons with the dielectric boundary of the sample. The magnetic flux is included in the expression for the spectrum of quasiparticles. The proximity effect and its influence on the modification of the spectrum of quantum coherent phenomena have been investigated. The behavior of cylindrical samples consisting of a superconducting (S) metal with a deposited thin pure normal (N) metal layer has been analyzed. In this structure the electrons are localized in a well bounded by a dielectric on one side and by a superconductor on the other. The specific feature of the generated quantized Andreev levels is that in the varying field H (or temperature T) each of the levels in the well can coincide periodically with the chemical potential of the metal. As a result, the state of the system experiences strong degeneracy and the density of states exhibits resonance spikes of the energy of the NS sample. This makes a significant contribution to the magnetic moment. A theory of the reentrant effect for NS structures has been developed, which interprets the anomalous behavior of the magnetic susceptibility of such structures as a function of the magnetic field and temperatures.